Nomadic Transmitter: Public Sphere and Aesthetics in Brazilian Media Activism - Novaes, Thiago O. S.; Caminati, Francisco Antunes [UNESP] (Ubiquity Press Ltd, 2019)
During the early 2000s a group of free radio activists in Sao Paulo, Brazil, commissioned the construction of an FM radio transmitter with multiple frequencies to offer radio workshops to communities interested in learning about radio language and practice. The transmitter was used by groups across Brazil and several South American countries. This article aims to describe and analyse over ten years of radio activism, taking as the object of reflection the agencies provided by a transmitter built in a computer case and adjustable in four frequencies in each locality in which it was activated. Considering the parameters of the Brazilian law on low-power radio that permits, under federal concession, 30 meters of antennae with 1km of radius and 25w of power, the objective was to present an experience of direct appropriation of radio spectrum for freedom of speech. Here we intend to discuss the construction of social media through which people meet to maintain shared infrastructures and to create radio language, transforming aesthetic mobilisation into an effective alternative to the control of the mainstream media over the use of the radio spectrum. Beyond subjective criticism about its ephemeral and often innocuous role when compared to constituted media powers, this paper aims to demonstrate that handling radio-frequency equipment can be a useful pedagogical tool to support the collective maintenance and repair of household autonomous communication equipment and infrastructure, in order to criticise and propose alternatives to media consumerist behaviours in different technological environments and situations.
Keywords: free radio; pedagogy; techno-aesthetics; situationism; imaginary futures; surveillance